ANALYSIS IN THE SYSTEM OF INFORMATION AND ANALYTICAL SUPPORT OF MANAGEMENT OF FINANCIAL RESULTS FROM OPERATIONAL ACTIVITIES - Чухліб, Алла (SWorldJournal, 2023)
The article defines and substantiates the components of information and analytical support systems, the applied aspect of analysis as an instrument for effective management of financial results from operational activities. Methodical aspects of analysis